Multiscale and multiphysics explorations of the transient deposition processes and additive characteristics during laser 3D printing. (30th June 2021) - Wei, H.L.; Liu, F.Q.; Wei, L.; Liu, T.T.; Liao, W.H.
Graphical abstract: Highlights: Laser DED were explored from the 1D track, the 2D layer, to the 3D full deposit. Convex, near-flat, and wavy builds were generated using various hatch spacings. The profiles of individual tracks and layers were extracted uniquely. Smaller hatch spacing caused lower remelting rate of vertically adjacent tracks. The individual tracks rotated with specific angles and formed distinct layers. Abstract: Laser directed energy deposition (DED) involves complex physical processes, and the trial and error examinations are time consuming and cost expensive. The research paradigm can be reshaped using advanced phenomenological models via computing the spatiotemporal variations of the build features. In this work, multi-layer and multi-track laser DED of Ti-6Al-4V were systematically explored on multiple scales including the 1D track, the 2D layer and the 3D full build considering the complex transport of energy, mass, and momentum in the moving freeform molten pool. The results showed that convex, near-flat, and wavy builds were generated using gradually larger hatch spacings. The profiles of individual tracks and layers were extracted through the unique advantages of the model. The individual tracks exhibited various patterns and rotated with specific inclinations to form distinct layer profiles. The net increments of the deposit generated upon the printing of a new track during the continuous deposition process showed that the smaller hatch spacing caused higher overlap rate of horizontally adjacent tracks but lower remelting rate of vertically adjacent tracks in neighboring layers. The 3D numerical model was validated with corresponding experiments for various process conditions. The scientific findings can provide useful insights for further researches of DED.